Finishing the finished human chromosome 22 sequence - Cole, Charlotte G (BioMed Central, 2008)
BACKGROUND: Although the human genome sequence was declared complete in 2004, the sequence was interrupted by 341 gaps of which 308 lay in an estimated approximately 28 Mb of euchromatin. While these gaps constitute only approximately 1% of the sequence, knowledge of the full complement of human genes and regulatory elements is incomplete without their sequences. RESULTS: We have used a combination of conventional chromosome walking (aided by the availability of end sequences) in fosmid and bacterial artificial chromosome (BAC) libraries, whole chromosome shotgun sequencing, comparative genome analysis and long PCR to finish 8 of the 11 gaps in the initial chromosome 22 sequence. In addition, we have patched four regions of the initial sequence where the original clones were found to be deleted, or contained a deletion allele of a known gene, with a further 126 kb of new sequence. Over 1.018 Mb of new sequence has been generated to extend into and close the gaps, and we have annotated 16 new or extended gene structures and one pseudogene. CONCLUSION: Thus, we have made significant progress to completing the sequence of the euchromatic regions of human chromosome 22 using a combination of detailed approaches. Our experience suggests that substantial work remains to close the outstanding gaps in the human genome sequence.